2015
DOI: 10.1016/j.ncl.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Therapies in Amyotrophic Lateral Sclerosis

Abstract: Synopsis Given the severity of their illness and lack of effective disease modifying agents, it is not surprising that most patients with ALS consider trying complementary and alternative therapies. Some of the most commonly considered alternative therapies include special diets, nutritional supplements, cannabis, acupuncture, chelation and energy healing. This chapter reviews these in detail. We also describe 3 models by which physicians may frame discussions about alternative therapies: paternalism, autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 192 publications
0
26
0
Order By: Relevance
“…Biomarker data and fish consumption frequency data suggest that mercury exposure is associated with ALS. As a cautionary note, prior work on chelation therapy with dimercaptosuccinic acid has not shown clinical benefit for patients with ALS, and use of sodium rather ethylenediamine tetraacetic acid has led to patient mortality . Participants with elevated toenail mercury levels had higher estimated methylmercury intake from fish consumption.…”
Section: Discussionmentioning
confidence: 97%
“…Biomarker data and fish consumption frequency data suggest that mercury exposure is associated with ALS. As a cautionary note, prior work on chelation therapy with dimercaptosuccinic acid has not shown clinical benefit for patients with ALS, and use of sodium rather ethylenediamine tetraacetic acid has led to patient mortality . Participants with elevated toenail mercury levels had higher estimated methylmercury intake from fish consumption.…”
Section: Discussionmentioning
confidence: 97%
“…CAM refers to a wide range of practices not traditionally included in the remit of the mainstream medical profession or medical curriculum [12]. Despite the widespread use of CAM among people with some neurodegenerative disorders [10,11], only one review paper focusing upon the clinical efficacy of CAM for ALS has been published to date [13]. This review reported the effect of most CAM as generally unproven with pockets of emerging evidence and highlighted conflicting evidence regarding the effect of dietary supplements, chelation therapy, and acupuncture for ALS management.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous new therapies are currently investigated [6], also including complementary medicine [7], and some of them may be promising. In the clinic of J.M., a plan of treating chronic diseases has been developed that involves eliminating risk factors, especially heavy metals, curing the sources of inflammation, and substituting with micronutrients and diets.…”
Section: Introductionmentioning
confidence: 99%